Lectin complement pathway gene profile of the donor and recipient does not influence graft outcome after kidney transplantation. - Damman, J; Kok, J; Snieder, H; Leuvenink, H; van Goor, H; Hillebrands, J; Dijk, v; Hepkema, BG; Reznichenko, A; van den Born, J; de Borst, M; Bakker, S; et al. (2012)
In kidney transplantation, complement activation was found to be induced by donor brain death, renal ischemia-reperfusion injury and allograft rejection. There are three known pathways of complement activation: the classical, lectin and the alternative pathway. The lectin complement pathway can be activated upon pattern recognition by mannan binding lectin (MBL) or ficolins (FCN). Single nucleotide polymorphisms (SNPs) in the genes encoding the lectin pathway proteins determine their functional activity and serum levels. The aim of this study was to investigate the role of the lectin gene profile of the donor and recipient on post-transplant outcome. A total of 12 functional SNPs in the MBL2, FCN2 and MBL-associated serine proteases 2 (MASP2) genes of 1271 donor-recipient pairs were determined. Lectin genotypic variants were analyzed for association with primary non-function (PNF), delayed graft function (DGF), biopsy proven acute rejection, death-censored graft survival and patient survival. Multivariate analyses found no association of donor and recipient MBL2 and MASP2 genotype with allograft outcome. Analysis of separate functional SNPs and haplotypes in the FCN2 gene of the donor and recipient did not reveal an association with transplant outcome. Also, the joint effect of the MBL2 and FCN2 genotype was not associated with allograft outcome.This study shows that the genetic profile of the lectin pathway of complement activation of the donor and recipient is not associated with allograft outcome after kidney transplantation.